Population structure and some growth properties of endemic Aphanius marassantensis Pfleiderer, Geiger & Herder 2014 in Süreyyabey Dam Lake, Turkey - Semra Benzer (Journal of Fisheries, 2021)
The present study was carried out to assess the population structure, growth and condition factor of Aphanius marasantensis Pfleiderer, Geiger & Herder 2014 in Süreyyabey Dam Lake, Turkey. The age of A. marassantensis ranged between 0+ and 3+ years. The sex percentage was determined as 62.30% males and 37.70% females. Total length and body weight of individuals ranged from 2.8 – 4.10 cm and 0.305 – 1.371 g respectively. The von Bertalanffy growth equations were calculated as Lt = 384.001 [1 – e–0.235 (t + 0.88)]; Wt = 1365.52 [1 – e–0.235 (t + 0.88)] 3.1217. The condition factor for all individual was 1.676.